Analisis Keuangan Daerah Terhadap Alokasi Belanja Modal Pemerintah Daerah Di Kabupaten Dan Kota Provinsi Sumatera Barat Tahun 2013 – 2017 - M Arif; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to look at regional financial independence, effectiveness of local government finance, efficiency and expenditure harmony on allocation of capital expenditure. The population in this study are all regency/city in sumatera barat as many as 19. The sample in this study using a sampling technique total sampling. Analyses were performed using multiple regression models. the results showed that partially, regional financial independence positive effect does not significantly on allocation of capital expenditure, effectiveness negative effect does not significantly on allocation of capital expenditure, efficiency positive effect significantly on allocation of capital expenditure, expenditure harmony positive effect significantly on allocation of capital expenditure, simultaneously regional financial independence, effectiveness of local government finance, efficiency and expenditure harmony significant effect on allocation of capital expenditure